Media's Influence on Citizen Demand for Public Goods - Keefer, Philip; Khemani, Stuti (Economic Development and Cultural Change, 2024)
Low voter interest in politicians who promise public goods is common in clientelist settings and a challenge to development. We show that access to media can increase interest. Households in Benin, responding to novel survey vignettes, generally support politicians who offer government jobs for a few at the expense of health and education for all. However, some households have exogenously greater access to community radio, which broadcasts programs designed to increase awareness of the importance of health and education. These households express significantly less support for clientelist politicians, indicating a role for media in shifting political equilibria away from clientelism.
Keywords: Citizens; Community Radio; Health and Education; Media's Influence; Politicians; Public Goods